2016
DOI: 10.4103/0253-7176.175089
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Indian Research on Co-occurring Psychiatric Disorders and Alcohol use Disorders

Abstract: Excessive use of alcohol has been identified as a major contributor to the global burden of disease. Excessive use of alcohol is a component cause of more than 200 disease and injury conditions. Alcohol use has been associated with increased morbidity and mortality across all regions of the world including South-East Asia. Epidemiological as well as clinic-based studies from Western countries have reported a high prevalence of co-occurrence of alcohol use disorder and psychiatric disorders. The research has es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…They also reported that psychosis and alcoholic hallucinosis are not uncommon. [10] Limitations Though the current study yielded a few positive findings, the following limitations must be kept in mind while interpreting the results.…”
Section: Family History Of Alcohol Dependencementioning
confidence: 85%
See 1 more Smart Citation
“…They also reported that psychosis and alcoholic hallucinosis are not uncommon. [10] Limitations Though the current study yielded a few positive findings, the following limitations must be kept in mind while interpreting the results.…”
Section: Family History Of Alcohol Dependencementioning
confidence: 85%
“…[9] A review article from Indian studies on the prevalence of various psychiatric co-morbidities among AUDs have reported that mood, anxiety, psychotic, and psychosexual disorders are commonly co-prevalent with AUDs. [10] Studies on the effect of age at onset of drinking on AUDs and their severity are quiet numerous in western research; however, similar studies are sparse and limited in Indian research. The only study similar to our study was published by Varma et al in 1994.…”
Section: Introductionmentioning
confidence: 99%
“…In previous Indian studies, 26-71 per cent patients with substance use disorders were found to suffer from co-morbid depressive disorders and 10-45 per cent from anxiety disorders. However, these studies were conducted on treatment seeking population34. Hence, patients with substance use disorders need to be actively screened for psychiatric disorders for timely diagnosis and management of co-morbid conditions, especially depression.…”
Section: Discussionmentioning
confidence: 99%
“…on dual diagnosis of substance use and psychiatric disorders was limited in comprehensiveness percentage patients of schizophrenia, and 80% of the patients of mood disorders (BPAD) were suffering and included only a limited number of Indian studies on the subject. [ 13 14 15 ]…”
Section: Introductionmentioning
confidence: 99%